Treatments for Convulsive and Nonconvulsive Status Epilepticus in Adults: An Expert Opinion Survey in South Korea - Byun, Jung-Ick (J Clin Neurol, 2021)
BACKGROUND AND PURPOSE: The aim of this study was to survey the expert opinions on treatments for convulsive status epilepticus (CSE) and nonconvulsive status epilepticus (NCSE) in adults. METHODS: Forty-two South Korean epileptologists participated in this survey. They completed an online questionnaire regarding various patient scenarios and evaluated the appropriateness of medications used to treat CSE and NCSE. RESULTS: Initial treatment with a benzodiazepine (BZD) followed by either a second BZD or an antiepileptic drug (AED) monotherapy was the preferred treatment strategy. More than two-thirds of the experts used a second BZD when the first one failed, and consensus was reached for 84.8% of the survey items. The preferred BZD was intravenous (IV) lorazepam for the initial treatment of status epilepticus. IV fosphenytoin and IV levetiracetam were chosen for AED monotherapy after the failure of BZD. The treatments for NCSE were similar to those for CSE. Continuous IV midazolam infusion was the treatment of choice for iatrogenic coma in refractory CSE, but other AEDs were preferred over iatrogenic coma in refractory NCSE. CONCLUSIONS: The results of this survey are consistent with previous guidelines, and can be cautiously applied in clinical practice when treating patients with CSE or NCSE.